Assistance In The Prevention of TBC Transmission With The Application of Appropriate Technology Using Cyclone Ventilator Modification (CVM) In The Houses Of Pulmonary TB and ISPA Patients As Well as PHBS Activities in Wonokusumo District - Rokhmalia, Fitri; rachmaniyah, Rachmaniyah; Khambali, Khambali (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
In Wonokusumo Village, 2022 saw a significant health challenge, with 186 cases of tuberculosis (TB) and 155 cases of acute respiratory infections (ARI) reported by the Health Department. This community service initiative aimed to reduce TB and ARI cases through promotional and preventive measures utilizing a modified cyclone ventilator (CVM). The CVM enhances indoor lighting and maintains optimal air circulation at a velocity of 0.15 m/s, in accordance with healthy housing regulations. Many homes in Wonokusumo are overcrowded and lack proper ventilation, with natural ventilation less than 15% of floor area. The close proximity of houses restricts light and air flow, and inadequate space conditions (rooms smaller than 4m² housing more than two occupants) contribute to unhealthy living environments. Implementing a healthy housing structure is vital for ensuring clean indoor air, which can prevent disease transmission, including TB. Our community service involved educating residents about maintaining clean and healthy homes, focusing on the importance of proper ventilation, lighting, and humidity control to mitigate TB and ARI risks. We distributed CVMs to three TB and ARI patients' homes, significantly improving knowledge about TB and ARI, as demonstrated by pre- and post-test results: TB knowledge rose from 20% to 94%, ARI from 18% to 90%, handwashing from 16% to 92%, and sanitation awareness from 14% to 90%. We recommend that the local health center promote health initiatives to reduce household transmission risks for TB. Overall, this initiative fostered improved public health awareness and contributed to enhancing community well-being in Wonokusumo